Long-term socioeconomic impact of the Nipah Virus encephalitis outbreak in Bukit Pelanduk, Negeri Sembilan, Malaysia: a mixed methods approach - Ng, C.W.; Choo, W.Y.; Chong, H.T.; Dahlui, M.; Goh, K.J.; Tan, C.T. (2009)
Background and Objective: In 1998/99, an outbreak of Nipah virus encephalitis occurred in several pig-farming communities in Malaysia. It was associated with a high mortality rate and persistent neurological deficits among many survivors. This mixed method study aimed to examine the long-term socio-economic consequences of the illness on affected pig farmers and their families in Bukit Pelanduk, Negeri Sembilan. Methods: A quantitative cross sectional survey was conducted in 2008 on 78 former patients or their kin from 61 households (46.2 males, mean age = 48.7 years) in Bukit Pelanduk via face-to-face interviews. This was followed by qualitative in-depth interviews with 20 respondents. Results: The immediate treatment costs were not a major burden to most households. Majority of the patients (92) required inpatient care and most obtained free care from public hospitals. Households relied mainly on savings and support provided by the public and family members during the outbreak. However, many former patients found their low educational qualifications prevented them from obtaining good alternative employment after their recovery. This had negatively affected their households' living standards. As a result, there had been a renewed appreciation of the value of education for their young, and one of their main concerns was the financial burden of educating their children. Conclusion: Free public health care protected most households from high medical costs. However, household living standards had dropped due to limited alternative employment opportunities. Education has been identified as a key to improving the long term welfare of affected households.